Comparative analysis of mechanical properties of paddy rice for different variety-moisture content interactions (International Journal of Agricultural Research, Innovation and Technology, 2024)
In recent years, postharvest loss has been a serious concern. However, knowledge of the mechanical properties is vital to developing any postharvest technology for rice production better. The objective of this research is to conduct a comparative analysis of the mechanical properties of selected paddy rice at different variety-moisture content interactions. The mechanical properties of AGRA rice, CRI-Amankwatia, CRI-Enapa, and CRI-Dartey, four local varieties developed in Ghana, are compared at 11.5%, 13.0% and 16.5% on wet basis moisture content. Tukey's Honest Significant Difference (HSD) comparisons test was conducted during data analysis to compare all possible pairwise combinations of the various varieties and moisture content interaction. From the results, it was concluded that CRI-Dartey, at 16.5%, recorded the highest Sphericity and Aspect Ratio of 0.391 mm3 and 0.298 mm3, respectively. For grain mass, AGRA rice at 13.0% also recorded 0.0312 g as the highest score. The GM1000, Angle of Repose and Bulk density CRI-Amankwatia at 16.5 % moisture content recorded the highest score of 29.33 g, 47.3o, and 654.0 kg/m3, respectively. AGRA rice at 13.0% observed the highest value of 1685.8 for kg/m3 true density, and the highest value for porosity was 70.83%, which was recorded by CRI-Enapa at 11.5 % moisture content. In all cases, the difference in mean value was less than the Least Square Difference. This indicates that there were no significant statistical differences between their mean values, indicating that technologies developed and adapted for one variety can equally be used for all the other varieties.Int. J. Agril. Res. Innov. Tech. 14(1): 18-29, June 2024